Age‐dependent hypoxia‐induced PD‐L1 upregulation in patients with obstructive sleep apnoea. Issue 7 (17th January 2019) - Cubillos‐Zapata, Carolina; Balbás‐García, Cristina; Avendaño‐Ortiz, Jose; Toledano, Victor; Torres, Marta; Almendros, Isaac; Casitas, Raquel; Zamarrón, Ester; García‐Sánchez, Aldara; Feliu, Jaime; Aguirre, Luis A.; Farre, Ramón; et al.
ABSTRACT: Background and objective: In obstructive sleep apnoea (OSA), intermittent hypoxia (IH) compromises immune surveillance through the upregulation of the programmed cell death‐1 (PD‐1) receptor and its ligand (PD‐L1). Because the risk of OSA‐related cancer depends on age, we assessed PD‐L1/PD‐1 expression in middle‐aged and older patients with OSA as well as in a murine model. Methods: PD‐L1 expression was studied in 41 patients with severe OSA and 40 healthy volunteers (HV), divided into two groups (≤55 and >55 years of age). We used flow cytometry, quantitative PCR (qPCR) and ELISA to determine PD‐L1 expression on monocytes and plasma PD‐L1 protein levels. Moreover, we analysed PD‐L1 expression on an in vivo IH model with old and young mice. Results: In subjects up to 55 years of age, severe OSA increased PD‐L1 surface protein and mRNA level expression on monocytes and soluble‐PD‐L1 protein concentration in plasma compared to HV. PD‐L1 and hypoxia‐induced factor (HIF)‐1α expression correlated with age in HV, whereas in patients with OSA there was a negative relationship. In the mice exposed to IH, PD‐L1 expression on F4/80+ splenocytes was also only increased in young animals. HIF‐1α expression was significantly higher in patients with OSA than in HV in subjects up to 55 years of age, while PD‐L1 expression in monocytes was related to HIF‐1α expression in young patients with OSA. Conclusion: PD‐L1 upregulation in patients with OSA as a consequence of HIF‐1α activation occurs mainly in young patients. In older patients with OSA, upregulation was not detected, possibly due to impaired oxygen sensitivity. Abstract : Hypoxia‐induced upregulation of the programmed cell death‐1 receptor and its ligand (PD‐L1) may explain associations between sleep apnoea and cancer. This link may be age‐dependent but, contrary to expectations, this study shows that PD‐L1 upregulation in sleep apnoea occurs mainly in younger patients. See related Editorial